Experimental and Numerical Investigation on Steel Fibrous Reinforced Concrete Slab Strips with Traditional Longitudinal Steel Bars - Pir, Arash (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: The aim of this thesis was to investigate the influence of steel fibers on mechanical performance of reinforced concrete slab strips based on experimental and theoretical research. Two different types of fibers that are having aspect ratio 60 and 80 have been employed with 4-four diverse volumetric percentages of 0.5, 1.0, 1.5, and 2.0% fibers. All the fibrous specimens have been compared to reinforced concrete slab strips without fibers and with identical longitudinal reinforcement. The flexural tests have been performed on slab strips to examine the effects of fibers on flexural improvement of specimens, and energy absorption enhancement. The dimensions of slab strips have been chosen to observe the flexural failure and prevent the shear failures. The results of experimental study have indicated that presence of fiber has been a significant influence on flexural performance and energy absorption. In theoretical modeling, by using the constitutive model of material that suggested by previous researchers and standards, the slab strips have been modeled via a FEA software namely, Abacus and analyzed. The results of numerical modeling have illustrated that the constitutive models are compatible with experimental test results quite satisfactorily. The experimental load-deflection curves verified that numerical stress-strain relationships for fibrous concrete material could be utilized for specimen with interaction by traditional reinforcement. Keywords: Steel fibers, Reinforced concrete, Flexural strength, Energy absorption capacity. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezin amacı çelik lif kullanılan betonarme plağın mekanik performansının deneysel ve teorik olarak değerlendirilmesidir. Bu amaç doğrultusnda iki farlı narinlik oranına sahip çelik lifler hacimsel olarak yüzde 0.5, 1.0, 1.5 ve 2.0 oranlarında kullanılarak betonarme plaklar deneye tabii tututmuştur edilmiştir. Çelik lifli betonarme plaklar klasik betonarme plak davranışı ile karşılaştırılarak çelik lif oranlarına bağlı mekanik özellikler değerlendirilmiştir. Bu doğrultuda, eğilme momenti etkisinin çelik lif kullanılarak iyileştirilmesi ve göçme durumunda enerji tüketme kabiliyetlerindeki artış irdelenmiştir. Deneyler için hazırlanan betonarme plak boyutu ve kullanılan donatı oranı deney numunelerinde sadece eğilmeye bağlı göçme durumu gözlenecek şekilde şekillendirilip kesme göçmesi önlenmiştir. Deney sonuçları çelik lif kullanımının betonarme plaklarda eğilme kapasitesinde önemli artış sağladığı ve enerji tüketme kapasitesinde de çiddi boyutta bir iyileşme gözlemlendiği görülmüştür. Teorik çalışma amacı için ise deneyler için hazırlanan numuneler ayni boyut ve yükleme şartlarında ve malzeme davranışı için önerilen bağıntılar kullanılarak Abakus yazılımı vasıtası ile sonlu elemanlar yöntemi ile modellenmiştir. Yapılan analiz neticesinde literatürde önerilen malzeme davranış ilişkilerinin oldukca iyi sonuçlar vermiştir. Deneysel çalışma sonuçları lifli betonlar için önerilen gerilme-birim şekil değiştirme bağıntılarının ayni zamanda klasik betonarme (donatılı) elemanların davranış kapasitesini belirlemede de kullanılabileceği yönunde olmuştur. Anahtar Kelimeler: Çelik lif, Betonarme, Eğilme Dayanımı, Enerji tüketme kapasitesi.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2013. Supervisor: Assist. Prof. Dr. Serhan Şensoy.
Keywords: Civil Engineering; Reinforced Concrete Construction; Steel Fibers - Reinforced Concrete - Flexural Strength - Energy Absorption Capacity